Generation Y’s Glance at The Connection Between Leadership and Well-Being - Kultalahti, Susanna (My University, 2011)
Occupational well-being has been the worry and interest of several researchers. Nowadays, the focus has shifted especially to young people, as they show increasing early retirement rates and sickness absences. That is both societal and organizational concern, which should be addressed proactively and assertively. The young generation in particular, Generation Y, possesses unique characteristics, that are said to revolutionize the whole working life. Nevertheless, this generation seems to perceive ill-being more than any other group. Fortunately, well-being can be managed and the supervisor can have a significant impact on how the well-being is promoted and taken care of. Thus, it can be estimated that, firstly, leadership and supervisor affect the subordinate’s well-being, and, secondly, Generation Y differs from other generations in this aspect. Therefore, the aim of this study is to examine the relationship between leadership and well-being, and further, differences between generations, especially concentrating to Generation Y and its perceptions of the leadership. A quantitative research design has been chosen to gain generalizable results and master the whole phenomena. Data (N = 7637) was collected by a large Finnish pension insurance company, who sent the questionnaire for its customer companies (36 companies). Thus, the data captures the essentials from Finnish working life and enables different statistical analyses. The main findings suggest that leadership and supervisor satisfaction have an influence on job satisfaction and well-being of the subordinate. These finding are in line with previous studies. Moreover, Generation Y had differences with other generations in job satisfaction as well as in supervisor satisfaction. In general, it seems that supervisors could utilize more their own actions in promoting well-being. In addition, the concentration in and efforts on the youngest employers are not overestimated. At the moment, they do not feel well, but are expected to work several decades as the careers are wished to expand.
Keywords: Well-being; Leadership; Generations; Generation Y; fi=Johtaminen ja organisaatiot|en=Management and Organization|